2022
DOI: 10.1097/md.0000000000030143
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary cryptococcosis after recovery from COVID-19 in an immunocompetent patient: A rare case report

Abstract: Rationale: Cryptococcus neoformans (C neoformans) infection typically occurs in immunocompromised patients infected with human immunodeficiency virus (HIV), or those taking immunosuppressive drugs, corticosteroids, or chemotherapy. Recently, there have been an increasing number of reports of cryptococcosis as opportunistic infections in COVID-19 patients, all of which have been related to immunocompromising conditions, underlying medical diseases, immune suppression drugs, or corticosteroids. Here, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…We had the similar findings that half (n = 8) of them were elderly and had underlying diseases, particularly for diabetes mellitus (n = 7). However, some patients did not have underlying diseases [ 17 , 23 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…We had the similar findings that half (n = 8) of them were elderly and had underlying diseases, particularly for diabetes mellitus (n = 7). However, some patients did not have underlying diseases [ 17 , 23 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Similarly, Regalla et al reported that in addition to two patients who had cryptococcosis diagnosed postmortem, the median time duration between COVID-19 diagnosis and Cryptococcus infection was 13 days (interquartile range [IQR], 5–49) in 11 patients [ 16 ]. Choi reported rare unusual presentation in an immunocompetent patient who developed culture-confirmed pulmonary cryptococcosis three months after COVID-19 [ 17 ]. Pulmonary and cerebral cryptococcosis were the most common form of COVID-19-associated cryptococcal infections, followed by disseminated and cutaneous infections [ 16 , 18 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 3 more Smart Citations